When calls the heart. Heart of truth [videorecording (DVD)]. - Loughlin, Lori; Lissing, Daniel, 1981-; Krakow, Erin; Wagner, Jack, 1959-; Oke, Janette, 1935-; Oke, Janette, 1935- (Shout Factory, 2017)
Life is always busy and full of challenges in Hope Valley. Abigail must deal with the railroad potentially coming to Hope Valley and the benefits and costs that would come with it. Elizabeth and Jack have volunteered to coach the kids in baseball, and Elizabeth works hard to inspire a young boy who is sure he cannot participate due to a leg injury. With her encouragement, the boy is able to find the courage to take part in the game.